The Casper Stent System for carotid artery stenosis. (11th January 2018) - Mutzenbach, Sebastian J; Millesi, Katharina; Roesler, Cornelia; Broussalis, Erasmia; Pikija, Slaven; Sellner, Johann; Machegger, Lukas; Griessenauer, Christoph J; Killer-Oberpfalzer, Monika
Abstract : Purpose: To report the results of a retrospective analysis of prospectively collected data evaluating the safety and efficacy of a double layer stent engineered for carotid artery occlusive disease. Methods: Between January 2014 and February 2017, 138 patients (25.4% women; median age 71 years) underwent Casper stent implantation for carotid artery stenosis. Eligibility criteria included stenosis >70% of vessel diameter (or >50% diameter with ulceration) in symptomatic patients or asymptomatic patients with >80% stenosis at the carotid bifurcation or in the proximal internal carotid artery. For all procedures, a distal embolic protection device was used. The primary endpoint was the rate of 90 day major adverse neurological events, defined as minor stroke, major stroke, or death by independent neurological assessment. Results: Stent deployment was completed successfully in all cases without documented technical failure. There were no adverse neurological events or mortalities within 90 days. One thromboembolic occlusion of a small distal branch of the anterior cerebral artery occurred during the procedure and resolved with systemic recombinant tissue plasminogen activator administration. New ischemic lesions, all clinically silent, were seen in 6.5% of patients on post-procedure cerebral MRI. Conclusion: The Casper carotid stent demonstrated safety and efficacy in the treatment of carotid stenosis, with no technical failures and no adverse neurological events seen throughout the 90 day follow-up period. Its double layer structure seems to combine adequate plaque scaffolding with high vessel adaptability.